Impacts of COVID-19 on an individual's leadership skill - Nur Alia Natasya Mohd Rafiq, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Leadership is a person's capability to accept, assess and convey information that benefits oneself and others. A leader learns and guides others toward personal growth and success. However, an individual does not develop this skill magically. One can learn and be trained to develop and hone the skill; however, not many have the privilege to do so. The majority of people would develop their self-leadership skills when they mature. Maturity happens when one faces life-changing events such as the Coronavirus Disease 19 (COVID-19) pandemic. The pandemic has significantly impacted an individual's self-leadership skills, which is what this research paper is based on. Multiple methods were used to assist and demonstrate the legitimacy of this article's research. The methods used are a survey and a literature review of articles on related topics. Research shows this life-changing event shows one's resilience in facing the challenges during the pandemic and how one reinvents oneself to overcome the odds.